FROM ELECTORAL FEDERALIZATION TO PROPORTIONAL REPRESENTATION. THREE REFORMING MOMENTS OF THE MEXICAN POLITICAL-ELECTORAL SYSTEM (1946, 1963 AND 1977) (Tzintzun, Revista de Estudios Históricos, 2023)
This paper studies the main innovations introduced into the Mexican politicalelectoralsystem by three reforms between the 1940s and 1970s, during theadministrations of Manuel Ávila Camacho (1940-1946), Adolfo López Mateos(1958-1964) and José López Portillo. (1976-1982). Our hypothesis proposes that,unlike other electoral reforms in the period from the promulgation of the 1917Constitution to the 1977 reform, these three moments of reform led tounprecedented constitutional changes, in which the opposition, even without asignificant presence and through various means, managed to introduce some oftheir proposals into the Chamber of Deputies. These three reforms were alsoinfluenced, to a greater or lesser degree, by the character of the six-year term inwhich they were developed, which helps to explain some of their characteristics.
Keywords: electoral reform; political system; electoral institution; elections